Inflammatory bowel disease in a colorectal cancer screening population: Diagnosis and follow-up. Issue 5 (May 2021) - Bezzio, Cristina; Manes, Gianpiero; Schettino, Mario; Arena, Ilaria; de Nucci, Germana; Della Corte, Cristina; Devani, Massimo; Mandelli, Enzo; Morganti, Daniela; Omazzi, Barbara; Pellegrini, Lucienne; Picascia, Desirée; et al.
Abstract: Background: Inflammatory bowel disease (IBD) is usually diagnosed in subjects with gastrointestinal symptoms, but may also be asymptomatic and diagnosed incidentally. Aims: to determine the prevalence of IBD in asymptomatic adults. Methods: we identified subjects who underwent colonoscopy between 1 September 2013 and 31 August 2019 in a regional colorectal cancer screening program with endoscopic findings suggestive of IBD, and retrieved their clinical, histological and therapeutic information. Results: 5116 subjects underwent colonoscopy, and 4640 persons were considered assessable. Of these, 54 (1.16%) had endoscopic findings suggestive of IBD, including 40 of Crohn's disease (CD) and 14 of ulcerative colitis (UC). A definite diagnosis of IBD was made in 19 patients, for an overall IBD prevalence of 0.41%, with 13 cases of CD (0.28%) and 6 of UC (0.13%). The mean follow-up was 26.8 months after the first colonoscopy. Therapy was started in 5 of 13 CD patients and all UC patients. Conclusion: Endoscopic findings suggestive of IBD are not infrequent in an asymptomatic colorectal cancer screening population. Visualization of the terminal ileum is recommended in this setting. A definite diagnosis of IBD was made in about 1 out of 3 subjects with endoscopic lesions. Most IBD patients had a mild form of disease, but some needed biologic therapy.